Neurodevelopment of Autism: Critical Periods, Stress and Nutrition - George Ayoub (Cells)
Autism spectrum disorder (ASD) is a neurodevelopmental disability that presents significant challenges in communication and behavior. ASD prevalence exceeds 2% among eight-year-old children and is at similar levels globally. We propose that critical periods during fetal development and early postnatal years establish the conditions for either neurotypical development or the emergence of autism through mechanisms that influence immune function or delay neuronal development. One critical period is characterized by the requirement for folate, a crucial methyl donor needed for DNA regulation. Insufficient folate availability has been linked to the risk of developing ASD. Another critical period may be affected by oxidative stress or inflammation of the fetal brain, potentially due to inadequate microglial immunity, which can lead to CNS inflammatory changes that disrupt typical neurodevelopment. We suggest that early supplementation with reduced folate and taurine during both the fetal and postnatal stages may be effective in mitigating the severity of ASD symptoms by promoting neurotypical development through these critical neurodevelopmental periods.